Review Artikel: Docking Molekuler Obat Anti Diabetes Melitus - Issabella Elsiana; Kholifatul Ulum; Klaritya Anisya Kurnia; Shafa Qotrunnada Widyatamaka; Shipa Paujiah (Journal of Pharmaceutical and Sciences, 2023)
Diabetes mellitus is a disease caused by damage to the pancreas organ such as insulin secretion abnormalities, insulin resistance, and insufficient production of the hormone insulin which can cause an increase in blood glucose levels. To overcome this, people with diabetes mellitus need antidiabetic drugs. In general, these drugs work by controlling sugar levels in the body. Although there are various therapeutic options for treating diabetes mellitus, there are often side effects that can be detrimental. Therefore there is a need for effective treatment, and the use of natural products is recommended as an alternative treatment method. This study aims to find natural product compounds that have medicinal potential as an alternative treatment for diabetes mellitus. The method used in this review is by searching published scientific literature in the form of PubMed, Elsevier journals, NCBI, and Google Scholar by differentiating the exclusions that have been set. The results of this review show positive results where there are various natural compound compounds that have potential as antidiabetic drugs. However, this is still limited to molecular docking, so further studies are needed.